2015
DOI: 10.1016/j.juro.2014.10.092
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis for Prevention of Febrile Urinary Tract Infections in Children with Vesicoureteral Reflux: A Meta-Analysis of Randomized, Controlled Trials Comparing Dilated to Nondilated Vesicoureteral Reflux

Abstract: Vesicoureteral reflux management is still controversial. In contrast to recently published studies and guidelines, this meta-analysis supports antibiotic prophylaxis in all children with vesicoureteral reflux regardless of reflux grade. More studies are needed to support this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Prophylaxis may be discontinued if VUR is not observed in the control imaging after the first year. If breakthrough infections occur under this antibiotic prophylaxis, surgical treatment should be attempted [16].…”
Section: Discussionmentioning
confidence: 99%
“…Prophylaxis may be discontinued if VUR is not observed in the control imaging after the first year. If breakthrough infections occur under this antibiotic prophylaxis, surgical treatment should be attempted [16].…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses studying the efficacy of CAP have been published since the RIVUR trial [2627]. The first meta-analysis by Wang et al [26] included 8 randomized, controlled trials [1516171819202128].…”
Section: Meta-analysis Post Rivurmentioning
confidence: 99%
“…There was no decrease in new renal scarring or difference in reported adverse events. de Bessa et al [27] analyzed 7 randomized, controlled trials comparing CAP and no prophylaxis/placebo in children with reflux [151617192021]. Analysis prior to RIVUR trial revealed benefit only to children with high-grade reflux, but addition of data from RIVUR study revealed pooled data that supports CAP in all children with reflux.…”
Section: Meta-analysis Post Rivurmentioning
confidence: 99%
“…24 After initial analysis of the trials, CAP was determined to be beneficial only in children with high-grade VUR (Grade III/IV). However, with the addition of the data from the 2014 RIVUR study, the new pooled data support CAP in all children with VUR to prevent recurrent UTI, regardless of reflux grade.…”
Section: Systematic Reviewsmentioning
confidence: 99%